A Study on High‐Quality RDX‐Based Flexible Explosives with High Energy and Low Vulnerability. Issue 39 (19th October 2022) - Liu, Bingxin; Li, Wantong; Chen, Shixiong; Qian, Hua; Liu, Dabin
Abstract: A new type of flexible explosive(HFE) with high energy and low vulnerability based on H‐RDX(High‐quality RDX) was proposed. Fundamental characterizations of H‐RDX, including infrared testing and particle size measurement, were carried out. The technological parameters of the process were researched. Mechanical sensitivities were characterized by impact sensitivity tester and friction sensitivity tester on the base of the explosion probability method. Energetic properties containing densities, initiation properties, and detonation velocities were investigated. For comparison, normal RDX was introduced. It is concluded that HFE with great flexibility was obtained under the sulfuration condition of 80 °C, 10d. The surface of H‐RDX is smoother with fewer defects and a smaller specific surface, leading to the better safety performance of HFE. The impact and friction sensitivities of HFE were 50 % and 22 % less than those of RDX‐based flexible explosive, respectively. Moreover, higher densities and a 6∼19 % rise in detonation velocities indicate that HFE(6700∼7500 m ⋅ s −1 ) has better energy performance. The precise incision was realized as the dosage of HFE rose(thickness, from 3 mm to 5 mm). The waterproofness of HFE was also tested by the detonation of the sample(submerged in 1 m water for 24 h) with the optimum proportion of the formula(explosive/rubber/functional agents=92/6/2). An excellent application prospect of the flexible explosive was observed in this work. Abstract : The preparation of flexible explosive(HFE) based on H‐RDX(a new kind of decreased sensitivity RDX) was carried out. The preparation process, safety properties, and energy levels of HFE were investigated, containing the selection of solvents, determination of sulfuration time, impact and friction sensitivity tests, detonation velocity tests, and so on. The waterproofness of this natural rubber‐based explosive was also tested. The findings indicate that HFE is a promising explosive that could satisfy the demand for high energy and low vulnerability in military and civilian applications.